2022
DOI: 10.3390/molecules27092610
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Cycloheterophyllin on Dinitrochlorobenzene-Induced Atopic Dermatitis in HaCaT Cells and BALB/c Mice

Abstract: Atopic dermatitis (eczema) is a condition that makes skin red and itchy. Though common in children, the condition can occur at any age. Atopic dermatitis is persistent (chronic) and tends to recur periodically. It may be accompanied by asthma or hay fever. No cure has been found for eczema. Therefore, it is very important to develop ingredients that aid the prevention and treatment of atopic dermatitis. Cycloheterophyllin is derived from Artocarpus heterophyllus and has antioxidant and anti-inflammatory activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Furthermore, WIF reduced serum IgE and TNF-α levels, which were elevated in the DNCB-induced group, alleviated epidermal and dermal thickness, and suppressed cell migration of inflammatory cells, such as eosinophils and mast cells. Based on these results, it can be considered that WIF exhibited anti-AD efficacy in a DNCB-induced AD-like mouse model [27]. Furthermore, WIF strongly inhibited ERK and p38 MAPKs activities and NF-κB-p65 translocation from the cytoplasm to the nucleus in the dorsal skin tissues of a DNCB-induced AD-like mouse model.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, WIF reduced serum IgE and TNF-α levels, which were elevated in the DNCB-induced group, alleviated epidermal and dermal thickness, and suppressed cell migration of inflammatory cells, such as eosinophils and mast cells. Based on these results, it can be considered that WIF exhibited anti-AD efficacy in a DNCB-induced AD-like mouse model [27]. Furthermore, WIF strongly inhibited ERK and p38 MAPKs activities and NF-κB-p65 translocation from the cytoplasm to the nucleus in the dorsal skin tissues of a DNCB-induced AD-like mouse model.…”
Section: Discussionmentioning
confidence: 82%
“…Many studies have shown that IFN-γ and TNF-α stimulate keratinocytes to induce signaling pathways involved in pro-inflammatory responses. Therefore, this model is often used as an in vitro test method for skin anti-inflammatory effectiveness [ 24 , 25 ]. It is shown in Figure 2 that once these pro-inflammatory cytokines (TNF-α and IFN-γ) are added, the formation of intracellular cytokine mRNA is significantly increased.…”
Section: Resultsmentioning
confidence: 99%
“…For the first time, in this study, the antioxidant effect of arzanol was natural extracts and compounds against oxidative stress in human epidermal cells and skin pathologies (Jiang et al, 2020;Mirata et al, 2023;Wang et al, 2022). In our experimental conditions, HaCaT cells were cultured in DMEM medium containing high calcium (Ca 2+ ) amount, a condition favorable for keratinocyte differentiation (Colombo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For the first time, in this study, the antioxidant effect of arzanol was evaluated in human HaCaT keratinocytes against the oxidative stress induced by H 2 O 2 with the aim of exploring its beneficial potential effects on human skin oxidative conditions. Cultured human HaCaT cells, being physiologically similar to normal human keratinocytes, represent a cell model amply used to assess the protective effect of natural extracts and compounds against oxidative stress in human epidermal cells and skin pathologies (Jiang et al, 2020; Mirata et al, 2023; Wang et al, 2022). In our experimental conditions, HaCaT cells were cultured in DMEM medium containing high calcium (Ca 2+ ) amount, a condition favorable for keratinocyte differentiation (Colombo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%